Pemberdayaan Kesehatan Mental Ibu dan Praktik Pemberian Nutrisi pada Anak Usia Dini - Natalia, Shanty; Radono, Panca; Maramba, Martinus; Mufidah, Nida Azhar; Araujo, Feliciano De; Daik, Jelli; Salma, Adevia; Laluna, Laila; Fitria, Henik Nur; Firdaus, Tsabitah Putri; Wardana, Ica Putri; Padaka, Serli Alisa; Kaka, Mersiana Ambu (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Early childhood development is a golden period that significantly determines the quality of life in the future. During this phase, maternal mental health plays a crucial role in the quality of child care and development. In Badalpandean Village, Ngadiluwih District, Kediri Regency, mothers' understanding of the importance of mental health and proper nutrition for toddlers was found to be low. This can negatively impact child development, necessitating appropriate educational interventions. Objective: The purpose of this service was increase mothers' knowledge about early childhood mental health and nutrition, teach practical strategies for maintaining mental health, and optimize the role of the Integrated Health Post (Posyandu) as a center for education and community empowerment. Method: This public service was conducted on July 31, 2025, at the Melati Posyandu Park in Badalpandean Village. Methods used included interactive lectures, group discussions, simulations, pretests, and posttests. Media used included PowerPoint presentations, leaflets, and other visual aids. Participants were 14 mothers with toddlers. Result: Pretest results showed that 42.86% of participants had good knowledge, 42.86% had sufficient knowledge, and 14.29% had insufficient knowledge. After the education, posttest results showed a significant increase, with 92.86% of participants having good knowledge, 7.14% having sufficient knowledge, and none in the insufficient category Conclusion: This community service activity successfully increased mothers' knowledge regarding mental health and nutrition for toddlers. It is recommended that similar activities be conducted on an ongoing basis and expanded in scope, involving Posyandu cadres and the village government for program sustainability.